The effect of soil chemical properties and plant nutrition on the growth of banana (Musa acuminata L.A. Colla) plants infected with Fusarium wilt - stronkhorstl@arc.agric.za (University of Pretoria, 2013)
Dissertation (MScAgric (Soil Science))--University of Pretoria, 2007.